Cognitive Transformation Through Brain jogging Exercise: A Longitudinal Study in Improving Working memory - Sholehudin, Indra; Fendrian, Ferry; Junanda, Hendya Alif; Heryanto, Mamat (Universitas Pendidikan Indonesia, 2025)
The purpose of this study was to determine the effect of Brain Jogging exercises on students' working memory ability. This study employed a pre-experimental design with a one-group pretest-posttest approach. Cluster random sampling was used to select participants. The sample in this study were students of class eight grade, which amounted to 29 people. The instrument used was the Merkaufgaben (ME) subtest from the IST (Intelligence Structure Test), designed to assess working memory. Data analysis in this study was performed using SPSS v20. The results of data processing analysis show that there is an effect of Brain Jogging exercises on working memory ability as evidenced by the difference in initial test results of 41.4% in the moderate category and 82.8% in the very high category after being given Brain Jogging exercises so that it can be concluded that there is a significant effect of Brain Jogging exercises on memory ability in junior middle school student in Bandung.